Immunogenetic Variation and Differential Pathogen Exposure in Free-Ranging Cheetahs across Namibian Farmlands - Castro-Prieto, Aines; Wachter, Bettina; Melzheimer, Joerg; Thalwitzer, Susanne; Hofer, Heribert; Sommer, Simone (PloS one, 2012)
Genes under selection provide ecologically important information useful for conservation issues. Major histocompatibility complex (MHC) class I and II genes are essential for the immune defence against pathogens from intracellular (e.g. viruses) and extracellular (e.g. helminths) origins, respectively. Serosurvey studies in Namibian cheetahs (Acinonyx juabuts) revealed higher exposure to viral pathogens in individuals from north-central than east-central regions. Here we examined whether the observed differences in exposure to viruses influence the patterns of genetic variation and differentiation at MHC loci in 88 free-ranging Namibian cheetahs. Genetic variation at MHC I and II loci was assessed through single-stranded conformation polymorphism (SSCP) analysis and sequencing. While the overall allelic diversity did not differ, we observed a high genetic differentiation at MHC class I loci between cheetahs from north-central and east-central Namibia. No such differentiation in MHC class II and neutral markers were found. Our results suggest that MHC class I variation mirrors the variation in selection pressure imposed by viruses in free-ranging cheetahs across Namibian farmland. This is of high significance for future management and conservation programs of this species.